FRASA NOMINA YANG BERFUNGSI SEBAGAI KOMPLEMEN DALAM KLAUSA BAHASA INGGRIS: Kajian Sintaksis - Lily Marliah (Jurnal Sosioteknologi, 2009)
The purposes of the research are: (i) to describe the type of the noun Phrase (NP) functioning as the complement in the English clause; (ii) to describe the structure of the constituents of the noun phrase functioning as the complement in the English clause; (iii) to describe the constituents that may be reduced, inserted, substituted, or transformed. The techniques used in the research are descriptive method with substitution. Permutation, deletion/reduction, and, paraphrase techniques. The research results are: (i) The types of noun or noun phrase (NP) functioning as the complement is common noun.;(ii) The structure of the English NP may consist of a noun as the head preceded by determiners (definite/indefinite articles), nouns (common, collective), adjective, conjunction as the pre-modifier; or noun as the head followed by preposition, definite article, adjective, noun, present participle phrase or noun clause, as the post-modifier, or the combination of the pre-modifier and post-modifier with the noun as the head; (iii) The constituents of NP may be expanded by adding certain constituents, inserted, deleted, substituted with the equivalent constituents, and transformed. Key words: noun phrase, structure, function, subject complement, object complement